Pengaruh Keaslian Merek dan Kredibilitas Influencer Terhadap Kepercayaan Merek Somethinc di Aster Kosmetik Malang - Naura Nabilla Khairunnisa; Farida Akbarina; Achmad Zaini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the influence of brand authenticity and influencer credibility on trust in the Somethinc brand at Aster Kosmetik in Malang. Somethinc’s market share, which dropped sharply from 59% in 2021 to 2.56% in 2025, indicates challenges in maintaining consumer trust, while previous studies have examined these two factors separately. This study employed a quantitative approach by distributing a questionnaire to 110 Somethinc consumers in Malang. The results show that brand authenticity and influencer credibility have a positive and significant effect on brand trust, both partially and simultaneously. These findings confirm that trust in a brand is not only shaped by product quality and consistency but is also influenced by how credible the influencers promoting it on social media are. This study provides insights for beauty industry players in designing more effective digital marketing strategies. Somethinc is advised to continue maintaining brand authenticity through product quality, transparent information, innovation, and honest communication. Additionally, collaborating with credible and experienced influencers should be prioritized to ensure that the reviews they share are convincing and that consumer trust remains strong.